Alterações epiteliais e cartilaginosas em cirurgia traqueal: estudo experimental em cobaias - Montovani, Jair Cortez [UNESP]; Nakajima, Victor [UNESP] (ABORL-CCF Associação Brasileira de Otorrinolaringologia e Cirurgia Cérvico-Facial, 2003)
FORMA DE ESTUDO: Experimental. MATERIAL E MÉTODO: Transplante homógeno de traquéia foi realizado em 51 cobaias (Cavia Porcellus). RESULTADO: Observamos reepitelização do enxerto a partir da traquéia receptora da cobaia, evoluindo de epitélio escamoso de 1 a 3 células nos animais com 3, 7 e 14 dias de observação para epitélio ciliado após 60 a 120 dias do transplante. A viabilidade do enxerto traqueal era boa, com reabsorção parcial da cartilagem e formação de estenose traqueal parcial, mas sem sinais clínicos evidentes de obstrução respiratória durante o tempo de observação dos animais.

STUDY DESIGN: Experimental. MATERIAL and METHOD: Tracheal homograft was performed in 51 guinea pigs (cavia porcellus) in order to study the graft epithelization. RESULTS: After the transplant procedure we observed reepithelization of the graft which initiated from the recipient trachea. The new formed epithelium was of squamous type and had 1 to 3 cell layers and was observed in animals with 3, 7 and 14 days after the surgical procedure. Respiratory epithelium with cilia was present with 60 and 120 days after the transplant. Cartilage absorption close to the tracheal anastomosis was the cause of partial tracheal stenosis in some animals. No clinical repercussion was noted due to this partial stenosis. Our conclusion was that tracheal homograft is an efficient surgical procedure for tracheal reconstruction.
Epithelial alterations in tracheal transplantation: experimental study in guinea pigs
Keywords: estenose; alterações epiteliais; transplante de traquéia; stenosis; epithelial alterations; tracheal homograf